Persistent disabilities 28 months after COVID-19 hospitalisation, a prospective cohort study - Bertrand Renaud; Richard Chocron; Guillaume Reverdito; Anne Blanchard; Thong Hua-Huy; Jean-Luc Diehl; Marine Livrozet; Marielle Subileau; Cédric Lemogne; Salma El-Batti; Edouard Auclin; Anne-Sophie Jannot; et al. (ERJ Open Research)
Background Limited data are available on long-term respiratory disabilities in patients following acute COVID-19. Patients and methods This prospective, monocentric, observational cohort study included patients admitted to our hospital with acute COVID-19 between 12 March and 24 April 2020. Clinical, functional and radiological data were collected up to 28 months after hospital discharge. Results Among 715 patients hospitalised for COVID-19, 493 (69.0%) were discharged alive. We could access complete medical records for 268 out of 493 patients (54.4%); 138 out of 268 (51.5%) exhibited persistent respiratory symptoms and agreed with the data collection and follow-up. Patients were predominantly male (64.5%), with a mean±sd age of 58.9±15.3 years. At the last follow-up, the leading symptoms were asthenia (31.5%), dyspnoea (29.8%) and neuropsychological symptoms (17.7%). Lung function improved up to the last visit. Mean diffusing capacity of the lung for carbon monoxide (DLCO) was 77.8% of predicted value, total lung capacity (TLC) was 83.5% and O2 desaturation during exercise (O2 desaturation) was 2.3%. While DLCO improved over the entire period, TLC improved in the early phase and O2 desaturation in the late phase. Except for those with lung comorbidities, only one patient presented with minor functional and chest radiological alterations at 28 months. Conclusion Patients with acute COVID-19 discharged alive showed improved clinical symptoms, lung function parameters and radiological signs up to 28 months post-infection. Persistent symptoms consisted mainly of asthenia and dyspnoea, with lung function returning to normal. One patient without prior respiratory issues exhibited moderate pulmonary fibrosis.